Role of Glycogen Synthase Kinase-3 in the Etiology of Type 2 Diabetes Mellitus: A Review - Bala, Asis; Roy, Susmita; Das, Debanjana; Marturi, Venkatesh; Mondal, Chaitali; Patra, Susmita; Haldar, Pallab K.; Samajdar, Gourav (Current Diabetes Reviews, 2022)
The risk of type 2 diabetes mellitus (T2DM) is increasing abundantly due to lifestyle-related obesity and associated cardiovascular problems. Presently, Glycogen synthase kinase-3 (GSK-3) has gained considerable attention from biomedical scientists to treat diabetes. Phosphorylation of GSK-3 permits a number of cellular activities like regulation of cell signaling, cellular metabolism, cell proliferation and cellular transport. Inhibiting GSK-3 activity by pharmacological intervention has become an important strategy for the management of T2DM. This review focuses on the schematic representation of fundamental GSK-3 enzymology and encompasses the GSK-3 inhibitors as a future therapeutic lead target for the management of T2DM that may significantly regulate insulin sensitivity to insulin receptor, glycogen synthesis and glucose metabolism. The various signaling mechanisms of inhibiting the GSK-3 by describing insulin signaling through Insulin Receptor Substrate (IRS-1), Phosphatidylinositol-3 Kinase (PI3K) and Protein Kinase B (PKB/ AKT) pathways that may hopefully facilitate the pharmacologist to design for antidiabetic drug evaluation model in near future have also been highlighted.
Keywords: glucose metabolism